Faktor-Faktor Yang Berhubungan Dengan Hyperemesis Gravidarum Pada Ibu Hamil Di Puskesmas Brayan - Evanirwana Evanirwana (Pusdikra Publishing, 2022)
Hyperemesis Gravidarum is defined as excessive nausea and vomiting in pregnant women with a frequency of> 10 times a day, causing disruption of daily acrivities and can even endanger the life of pregnant women and if not treated can even cause death. This study aims to determine the factors associated the hyperemesis gravidarum to pregnant women of Brayan Public health center in 2019. This research is a quantative study with a cross sectional study approach. The population in this study were all pregnant women in the first and second trimesters who visited the KIA Poli in Brayan Public health center for the period January-February 2020. The total sample was 99 people with the sampling technique using random sampling. The research instrument was a questionnaire and a Food Frequency Questionnaire (FFQ). Data analysis with chi-square test. The result showed that there was a relationship between the knowledge of pregnant women and hyperemesis gravidarum at Brayan Public health center in 2019 with X2 65.663 and a p-value of 0.000, there was a relationship between the attitudes of pregnant women and hyperemesis gravidarum at Brayan Public health center in 2019 with X2 67,210 and p-value 0.000, there is a relationship between the support of husbands of pregnant women with hyperemesis gravidarum at Brayan Public health center in 2019 with X2 62,561 and p-value 0.000, there is a relationship between parity of pregnant women and hyperemesis gravidarum at Brayan Public health centter in 2019 with X2 14,588 and p-value 0.000 and there is a relationship between the diet of pregnant women and hyperemesis gravidarum at Brayan Public health centre in 2019 with X2 87,332 and a p-value of 0.000.